1977
DOI: 10.1002/qua.560120408
|View full text |Cite
|
Sign up to set email alerts
|

Simplifications in the generation and transformation of two‐electron integrals in molecular calculations

Abstract: AbSbCtSApproximate numerical linear dependence among the columns of the two-electron integral matrix and the positiveness of the Coulomb operator are exploited in order to reduce the number of integrals that need to be calculated when a numerical accuracy is given by the machine in use or by the choice of the investigator. Numerical results presented indicate that the method leads to an algorithm for carrying out the two-electron integral four-index transformation which in practice can be achieved in a small f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
516
0
1

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 484 publications
(521 citation statements)
references
References 27 publications
1
516
0
1
Order By: Relevance
“…Beebe and Linderberg demonstrated that CD of two-electron integrals can also be thought of as the determination of a linearly dependent set of atomic orbital product functions, [196] which are commonly referred to as the Cholesky basis, and it is very important to note that using a Cholesky basis as an ABS makes CD and DF formally equivalent. Early CD implementations were significantly more expensive than DF as they still required four-center two-electron integrals to be evaluated, and the Cholesky basis had a strong dependence on molecular geometry.…”
Section: Auxiliary Basis Setsmentioning
confidence: 99%
“…Beebe and Linderberg demonstrated that CD of two-electron integrals can also be thought of as the determination of a linearly dependent set of atomic orbital product functions, [196] which are commonly referred to as the Cholesky basis, and it is very important to note that using a Cholesky basis as an ABS makes CD and DF formally equivalent. Early CD implementations were significantly more expensive than DF as they still required four-center two-electron integrals to be evaluated, and the Cholesky basis had a strong dependence on molecular geometry.…”
Section: Auxiliary Basis Setsmentioning
confidence: 99%
“…On the other hand, if we consider an isolated atom, the CD of its ERI matrix 36 provides an upper bound for the value of ⌬ min , Eq. ͑3͒,…”
Section: Atomic CD Auxiliary Basis Setsmentioning
confidence: 99%
“…35 With this spirit and with the additional aim at rectifying the drawbacks of the standard auxiliary basis sets, three of the present authors proposed 63 to merge the DF approximation with the Cholesky decomposition ͑CD͒ approximation of Beebe and Linderberg. 36 The latter had been around for about 30 years as the forgotten twin brother of the DF method. Although CD presented some advantages over the DF approximation, strict error control in particular, it did not become popular.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The algorithm is designed to avoid storage, in core as well as on disk, of four-index intermediates along the lines deviced by Hättig and co-workers [10][11][12][13][14] for the RI-CC2 method. Through examples involving as many as 2.8 billion coupled cluster doubles amplitudes, we have demonstrated the large-scale applicability of the implementation.…”
Section: Summary and Concluding Remarksmentioning
confidence: 99%